Parallel Imports and Repair Services - Jota Ishikawa; Hodaka Morita; Hiroshi Mukunoki (Center for Economic Studies and ifo Institute (CESifo), 2018)
This study explores the effect of parallel imports (PIs) when the producer may discriminate repair and maintenance services against PI units. This service discrimination weakens intra-brand competition and reduces the degree of price convergence between countries. If the producer makes costly activities to improve the quality of the good, permitting PIs in the presence of the service discrimination could lower the quality, because lower quality leads to a larger price gap. Consequently, it is possible that prices increase, consumers lose, and welfare deteriorates in both countries. This negative welfare effect is more likely to emerge as trade liberalization proceeds.
Keywords: F12; F13; F10; D42; L41; 330; parallel imports; service discrimination; goods quality; welfare; trade liberalization